Ameliorating Precast Concrete Curbs Using Rubber and Nano Material - Komaki, Mohammad Ebrahim; Ghodrati Dolatshamloo, Amirreza; Eslami, Mahdi; Heydari, Sahar (Civil Engineering Journal, 2017)
Disposal of waste tire rubber has become one of the major environmental issues in each part the World. One of the possible solutions to dispose of scrap tire rubber is using them into concrete curbs. This paper presents a new method to ameliorate the rubber concrete using a particular rubber size and Nano Material. Initially six mix designs were performed to determine the optimized size and percentage of rubber according to compressive strength. Afterwards, the major concrete curbs were made with the optimum mix design. Three different samples were made to determine the effects of rubber and Nano. One of which was made without rubber and Nano, the other was made with rubber and the last with rubber and Nano. Experiments were carried out to determine the durability and strength of specimens according to ISIRI-12728.